Faktor – Faktor yang Mempengaruhi Keberhasilan Pemberian ASI Eksklusif pada Ibu yang Bekerja di Puskesmas Batahan Kec. Batahan Kab. Mandailing Natal Tahun 2022 - Yulita Liana Lubis; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Anggun Sipahutar (Inovasi Kesehatan Global, 2024)
Exclusive breastfeeding or exclusive breastfeeding is a baby who is given only breast milk, without additional fluids such as formula milk, orange, tea, water, Exclusive breastfeeding is recommended for a period of at least six months, and after six months the baby is introduced to solid foods. While breast milk can be given up to the age of two years or more. The purpose of this study is to analyze the factors that influence the success of providing exclusive breastfeeding to mothers who work at the Batahan Health Center, Batahan District, Mandailing Natal Regency in 2022. The type of research is Descriptive Analytical with a research design using cross sectional, namely research conducted with momentary observation in a certain period of time and each subject is only observed once. This research was conducted at the Batahan Health Center, Batahan District, Mandailing Natal Regency With the consideration as a place where at the Batahan Health Center, Batahan District, Mandailing Natal Regency. The population in this study was 20 mothers, then the sample was part of the entire object studied and was considered to represent the entire population, the number of samples used was 20 respondents with a total sampling technique. The data collection technique used a questionnaire sheet and a respondent observation sheet. The results of the statistical test using Chi-square (p-Value) of 0.01 <0.05, there was a significant relationship between the factors of Age, Knowledge, Attitude and Work Environment with the provision of Exclusive Breastfeeding at the Batahan Health Center, Batahan District, Mandailing Natal Regency in 2022.